Interlingual Errors And Intralingual Errors Found In The English Narrative Text Written By Smp, Smk And University Students' In Lampung - Sari, Eny Maulita Purnama; , Prof. Dr. Endang Fauziati, M.Hum; , Muamaroh, Ph.D (2015)
Abstract The current study investigates the interference of L1 (Indonesian) into L2 (English) and the errors that occur due to the influence of TL (target language). The focus of the study is on the errors committed by these EFL students in writing narrative text and emphasized on interlingual errors and intralingual errors. The objectives of the study are to investigate the errors committed by these EFL students in order to find out; (1) the types of interlingual errors and intralingual errors in Junior High School, Senior High School and University, (2) the frequencies of interlingual errors and intralingual errors in Junior High School, Senior High School and University, and (3) the similarities and differences of interlingual errors and intralingual errors in Junior High School, Senior High School and University. The researcher used Qualitative descriptive as the method design. The data collecting technique was writing test. The data was errors sentence that found in the students' narrative writing. The subjects of the study comprised 30 eight grade of SMP Muhammadiyah Pekalongan, East Lampung and 30 eleven grade SMKN 1 Pekalongan, East Lampung, and 30 fourth-year students of English Department of University of Muhammadiyah, Metro Lampung. The findings of the study suggest: (1) The types of interlingual errors and intralingual errors made by SMP, SMK and University students were divided into 2 levels, they are morphological level and syntactical level. (2) the frequency of interlingual errors in Junior High School 36 cases (30.26%), in Vocation High School 39 cases (36.77%) and 9 cases (10.98%) in University. The frequency of intralingual errors in Junior High School 83 cases (69.74%), in Senior High School 70 cases (64.23%) and 73 cases (89.02%) in University, and (3) The similarities of interlingual errors and intralingual errors found in Junior High School, Vocation High School and University are 2 types in morphological level; they are the use of L1 structures and omission of BE in nominal sentences. Also 2 types in syntactical level; they are the use of presen BE in past event and the use present Verb in past event. The differences of interlingual errors and intralingual errors found in SMP, SMK and University are (1) in SMP there are 8 types errors that found in the students' writing, (2) 3 types of errors that found in SMK, and (3) 2 types of errors found in University. Keywords: Interlingual Errors, Intralingual Errors, Comparative Taxonomy